Pengaruh Literasi Keuangan, Financial Technology, Persepsi Risiko, dan Locus of Control Terhadap Keputusan Investasi Pengusaha Muda - Nur Fadila; Goso Goso; Rahmad Solling Hamid; Imran Ukkas (Owner : Riset dan Jurnal Akuntansi, 2022)
Financial literacy refers to the skills and measures of objective knowledge and individual expertise related to the management and decisions of personal finance. The complexity of financial instruments and the development of information technology are increasing. Many studies find that individuals, in general, have limitations and a lack of information on basic financial principles. The study aims to test and analyze the influence of financial literacy, financial technology, risk perception, and locus of control on young entrepreneurs' investment decisions. The analysis unit in this study is a young entrepreneur in northern Luwu County. Primary data was obtained through the dissemination of questionnaires involving 250 respondents. The data analysis technique used is multiple regression linear analysis. This study shows that financial literacy and locus of control have a significant influence on investment decisions. As for the variables of financial technology and risk perception, they did not significantly affect the investment decisions of young entrepreneurs.